2023
DOI: 10.3390/antiox12091674
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Diet and Oxidative Stress in the Pathogenesis of Lymphoproliferative Disorders

Gabriella Cancemi,
Nicola Cicero,
Alessandro Allegra
et al.

Abstract: Lymphomas are a heterogeneous group of pathologies that result from clonal proliferation of lymphocytes. They are classified into Hodgkin lymphoma and non-Hodgkin lymphoma; the latter develops as a result of B, T, or NK cells undergoing malignant transformation. It is believed that diet can modulate cellular redox state and that oxidative stress is implicated in lymphomagenesis by acting on several biological mechanisms; in fact, oxidative stress can generate a state of chronic inflammation through the activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 206 publications
0
5
0
Order By: Relevance
“…HO • is the most reactive and oxidative ROS, and it can induce lipid peroxidation with polyunsaturated fatty acids, resulting in the production of ROO • . After a reaction with chloride ions and in the presence of myeloperoxidase, H 2 O 2 is also used to produce additional microbicide ROS, namely, HOCl [50,51]. A comprehensive review of the results obtained in this investigation revealed that, among the extracts examined, the hydroalcoholic extract has a higher scavenging effect against the assessed ROS and RNS (Table 3).…”
Section: Reactive Oxygen and Nitrogen Speciesmentioning
confidence: 85%
See 2 more Smart Citations
“…HO • is the most reactive and oxidative ROS, and it can induce lipid peroxidation with polyunsaturated fatty acids, resulting in the production of ROO • . After a reaction with chloride ions and in the presence of myeloperoxidase, H 2 O 2 is also used to produce additional microbicide ROS, namely, HOCl [50,51]. A comprehensive review of the results obtained in this investigation revealed that, among the extracts examined, the hydroalcoholic extract has a higher scavenging effect against the assessed ROS and RNS (Table 3).…”
Section: Reactive Oxygen and Nitrogen Speciesmentioning
confidence: 85%
“…•− , neutralizing the effects of this ROS; through hydrogenation; or by complexing with oxidant species [21,50,52]. In terms of RNS-scavenging capacity, all of the extracts proved to be effective scavengers of both • NO and ONOO − .…”
Section: Reactive Oxygen and Nitrogen Speciesmentioning
confidence: 97%
See 1 more Smart Citation
“…Both the nanomaterials revealed antioxidant activity, attesting to their implication in a plausible reduction of oxidative stress following microbial infection. Accumulating evidence has shown the involvement of oxidative stress in the pathogenesis of several diseases [69,70]; thus, the intervention of antioxidants during an infectious condition might prevent cell damage induced by oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has demonstrated OS's role in both the pathophysiology and response to specific therapies of hematological disorders [11][12][13][14][15][16][17][18][19]. Several aspects of CML have been linked to OS, including dominance of one or more malignant clones or subclones, DNA alteration and defective DNA repair, antiapoptotic effect of p210 protein, and genomic instability in hematopoietic stem cells associated with bcr-abl oncoprotein [20][21][22].…”
Section: Introduction 1general Consideration On Chronic Myeloid Leuke...mentioning
confidence: 99%